An Approach on Biomarkers for Carcinoma Meningitis in Solid Tumors - Ashish Manne; Ravi Paluri (Highlights on Medicine and Medical Research Vol. 2, 2021)
Carcinomatous meningitis (CM), also known as neoplastic meningitis or leptomeningeal metastasis, refers to the invasion of meninges protecting the brain and spinal cord by tumor cells. It should be distinguished from brain metastasis where there is an infiltration of brain parenchyma by metastatic cells. With improved overall survival in a majority of cancers with advances in cancer management, more cases of CM are being diagnosed lately. Cancer cells from the primary source can migrate to the meninges through various ways: vertebral and paravertebral metastasis (breast and lung cancers), perineural spaces (gastrointestinal cancers), arteries from parenchymal metastasis, and rarely by direct invasion (primary central nervous system tumors). Patients often present with non-specific symptoms, like a headache and altered mental status, or focal neurological signs, depending on the area of the central nervous system involved. Due to poor prognosis and limited success in treating it, early detection is key. Diagnosis in suspected cases by cerebrospinal fluid (CSF) cytology (identifying malignant cells) and/or imaging has limited success. In this review, we discuss the need for using various biomarkers in CSF to increase the probability of a diagnosis of CM in solid tumors. Biomarkers can also help in predicting the disease burden, response to treatment, and in detecting the recurrence. We also discuss utilizing Fluorescence in situ hybridization (FISH), Rare cell capture technology (RCCT) and circulating tumor DNA (CtDNA) in identifying malignant cells in CSF for diagnosing CM. However, the definitive role of these modalities in combination needs further validation in larger cohorts.